An assessment of radiation oncology medical physicists’ perspectives on undertaking research - Ebert, M.; Halkett, Georgia; Berg, M.; Cutt, D.; Davis, M.; Hegney, D.; House, M.; Krawiec, M.; Kearvell, R.; Lester, L.; Maresse, S.; McLoone, P.; et al. (2016)
As part of a study of the radiation oncology workforce, radiation oncology medical physicists (ROMPs) who had worked in Australia were surveyed regarding their attitudes to participating in research. Responses from 88 ROMPs were available for analysis, representing a broad mix of employment situations and research experience. Greater than 70% of ROMPs described their involvement in research as “liking it” or “loving it”, with associated identified benefits including skills development, job satisfaction and career progression. Over half of respondents agreed that involvement in research inspired them to stay in their profession. However, lack of time, support and motivation were all identified as barriers to participation in research. Areas of research interest were identified. This study highlights the importance of a research culture for job satisfaction and staff retention.